Research on the Influence Mechanism of Consumers’ Perceived Risk on the Advertising Avoidance Behavior of Online Targeted Advertising - Wang, Hai Jian; Yue, Xia Lei; Ansari, Aisha Rehman; Tang, Gui Qian; Ding, Jian Yi; Jiang, Ya Qiong (Frontiers in Psychology, 2022)
In China, online sales continue to grow against the generally adverse effects of the Covid-19 pandemic on economic development. Although advertisers favor online targeted advertising for its precision, consumers may find it intrusive and avoid it. This study constructed a conceptual model based on Stimulus-Organism-Response(SOR) theory,Approach-Avoidance Theory and Brand Avoidance Theory to investigate the influence mechanism of consumers’ perceived risk on the avoidance behavior of online targeted advertising via an online survey.Collected 436 validated data was analyzed through structural equation method in AMOS statistical software.Results showed that the positively influenced advertising avoidance,and negative emotions mediated the relationship between perceived performance risk, time-loss risk, freedom risk, and advertising avoidance,but perceived privacy risk did not influence advertising avoidance through negative emotions. Perceived Covid-19 risk moderates the effect of negative emotions on advertising avoidance.The findings provide important insights for helping governments,advertisers and online platforms into which risk perceptions influence advertising avoidance,and suggests ways to mitigate consumers risk perceptions for the mutual benefit of brands and users.